(untitled) (TAJ: Journal of Teachers Association, 2009)
Image guided FNAB of pulmonary lesions are widely applied now a days. Most of the lesions which are located nearer to the chest wall can be well visualized by ultrasonography. Whereas smaller lesions, deeply located ones, mediastinal or juxtra-hilar lesions may not be visualized sonographically. In those cases CT-guidance becomes beneficial. We report 127 FNABs done during a 2 year period. In considering the poor economic ability of the patient USG-guidance was preferred provided the lesion could be well visualized. Ultrasound guided method was successfully performed in majority of cases except a few where CT-guidance was necessary. After first aspiration an immediate cytological assessment was done by a quick staining method and in case of inadequacy of the specimen a second pass was made within an hour. Different pathological spectrum of diseases was diagnosed cytologically and was compared with their final diagnosis. Negligible immediate or late complications were noticed. Image guided FNAB of intra-thoracic masses can therefore be made with minimum complication, can allow the physician to decide the mode of treatment in a shortest possible time and in most of the cases an ultrasound guidance is sufficient enough to meet the poor economic status of people in this subcontinent. doi: 10.3329/taj.v20i2.3070 TAJ 2007; 20(2): 110-115